Cardiac rehabilitation after acute coronary syndrome comparing adherence and risk factor modification in a community-based shared care model versus hospital-based care in a randomised controlled trial with 12 months of follow-up. (April 2017) - Bertelsen, Jannik B; Refsgaard, Jens; Kanstrup, Helle; Johnsen, Søren P; Qvist, Ina; Christensen, Bo; Christensen, Kent L
Aim: To investigate whether phase II cardiac rehabilitation (CR) conducted by a community model of shared care CR (SC-CR) including health care centres and general practice was feasible and provided acceptable results and to compare SC-CR to hospital-based CR (H-CR) in a randomised controlled trial. Methods: Patients were randomised to H-CR or SC-CR after admission for acute coronary syndrome. In SC-CR, the general practitioner took over the responsibility of the remaining rehabilitation, pharmacological treatment and risk factor management after the initial visit to the hospital outpatient clinic. The Municipal Health Care Centres provided courses on smoking cessation, nutrition, and exercise training and contributed to disease education and psychosocial support. The main endpoint was adherence to the CR programme and compliance with lifestyle modifications. Results: In total, 1364 patients were screened, 327 (24%) were eligible, and 212 (65%) accepted participation. Phase II CR was completed by 192 (91%) of the participants. Full adherence to the CR programme was seen in 53% in SC-CR versus 54% in H-CR (relative risk (RR): 0.98, 95% confidence interval: 0.73–1.32). In H-CR, patients had higher rates of adherence to dietary advice and health education. In SC-CR, 12% of patients did not attend the risk factor evaluation and clinical assessment with their general practitioner. No difference in risk factor improvement was found. Exercise training was declined by 25% in both groups. Conclusion: Adherence to phase II CR was high in both groups. SC-CR did not improve adherence and efficacy, but had comparable effects on medication and risk factors. Thus, SC-CR was safe and effective.